An Educational Overview of Ultrasound Probe Types and Their Fields of Application - DE LUCA, Ramona; FORZONI, Leonardo; GELLI, Francesca; BAMBER, Jeffrey (Archives of Acoustics, 2021)
The ultrasound (US) imaging market is fast-changing in terms of needs, trends and tendencies as it undergoes rapid innovations. Due to technological improvements, a variety of US probe types is available to cover a wide range of clinical applications. The aim of this paper is to provide information to healthcare professionals to select the appropriate probe for the intended use and the desired performance/price ratio. This work describes the majority of conventional, special and unique US probe types currently available on the market, together with technological insights that are responsible for image quality and a list of some of their clinical applications. The description of the inner transducer technologies allows to understand what contributes to different prices, features, quality level and breadth of applications. The comparison of current US probes and the analysis of advanced performances arising from the latest innovations, may help physicians, biomedical and clinical engineers, sonographers and other stakeholders with purchasing and maintenance commitments, enabling them to select the appropriate probe according to their clinical and economical needs.